'OPEN MARKETING SYSTEM' AS A WAY OF INNOVATIVE ENTERPRISE SUPPORTING - Maria V. KOLGAN; Pavel L. KOLGAN (Advanced Engineering Research, 2010)
The creation of 'open marketing system' which can help a modern and active enterprise to respond dynamically to market changes is suggested. Open Source taken as a basis is a new marketing mix to supply and implement an innovative product or service.